Civil Religion as a Normative Framework for Preventing Radicalism in Indonesia: Integration of Pancasila and Deliberative Democracy —Öffentlichkeit - Muhammad Faizal Zaky Mubarok; Raihan Aqshal Arighi; Yusuf Zaenal Abidin (Prodi Magister Sosiologi UIN Sunan Gunung Djati Bandung, 2026)
Existing studies on radicalism and terrorism emphasize security, legal, and ideological lenses, framing it solely as a state threat, while overlooking its normative, symbolic, and moral appeals that foster societal legitimacy. This research analyzes radicalism as a crisis of civic integration and state moral delegitimization, proposing civil religion—synthesizing Durkheim's social facts, Rousseau's social contract, Bellah's civil religion, and Habermas's deliberative democracy—as a preventive framework treating radicalism as counter-civil religion. Through qualitative literature analysis, findings show civil religion builds public ethics, social cohesion, and cultural deradicalization by reframing violence, substituting identities, and integrating religion-nation symbols; in Indonesia, Pancasila embodies this, countering radicalism via inclusive identity, moral legitimacy, and deliberative pluralism alongside social justice, transcending mere securitization.